Qualidade de frutos de Passiflora cincinnata em diferentes épocas de colheita sob cultivo irrigado e sequeiro - Sales, Giuliana Naiara Barros (2024)
The wild passion fruit (Passiflora cincinnata) is a species known for its water resistance, pests, and diseases common to the yellow passion fruit (Passiflora edulis). The desirable agronomic characteristics of the wild passion fruit, along with the flavor, aroma, and longevity of the fruits, have allowed for an increase in its production. Embrapa recently released the cultivar 'BRS Sertão Forte', which stands out for its low production cost, yielding fruits with durability, resistance to handling, and transportation. The bottleneck for large-scale production of this species is identifying the point of maturity at which the fruits express their full potential, considering that one of the criteria used to determine harvesting, such as color, remains unchanged even after maturity. Therefore, the objective was to evaluate the fruit quality of P. cincinnata at different harvest times under irrigation and rainfed conditions, with an experimental design in randomized blocks of 4 x 2 (8 treatments) and five replicates. Post harvest characterization was assessed to ensure fruit maturity. In general, fruits of P. cincinnata cultivar 'BRS Sertão Forte' should be harvested at 80 days after anthesis under irrigated cultivation to improve physical characteristics. Wild Passiflora cincinnata fruits should be harvested at 100 days after anthesis under irrigated cultivation to improve chemical characteristics.